Att bekämpa det onda eller främja det goda: Fyra verksamhetsperspektiv på individer i våldsbejakandemiljöer samt preventionsarbete runt dessa (Sociologisk Forskning, 2016)
To fight evil or promote good: Four organizational perspectives on individuals inviolent environments and prevention work around them.The purpose of this article is to examine organizational understandings and perceptions that can affect the current work with defectors from and members in violent and extremist environments. The empirical material consists primarily of answers to open questions in a survey, where professionals from four organizations are represented: social services, school, police and politics. The material is analyzed with direct qualitative content analysis and shows two contradict approaches to the problem; one that argues for ”fighting the evil” and another that argues for ”promoting the good”. The theoretical framework presented is Erving Goffmans’ frame analysis, Howard S. Beckers’ labelling process and Ingrid Sahlins’ discussion about different kinds of prevention strategies. The results show how organizational understandings and perceptions are far from uniform but rather disparate, and also that assumptions made by professionals have wide implications – often related to morally based approaches grounded on notions of good and evil.
Keywords: ideological extremism; framing; labelling; organizations; prevention